Allometric Model for Estimating Above-ground Biomass and Carbon Stock of Bambusa vulgaris var. striata - Mulyana, Budi; Wirabuana, Pandu Yudha Adi Putra; Hadi Purwanto, Ris (Jurnal Manajemen Hutan Tropika, 2025)
Bamboo, one of the non-timber forest products, is promising in climate change mitigation strategy due to its ability to remove CO2 from the atmosphere through photosynthesis. However, the allometric model to estimate the biomass and carbon of bamboo is still limited. The research aimed to develop the allometric model using the diameter as the predictor. The materials for destructive sampling were 30 culms of yellow ampel bamboo (Bambusa vulgaris var. striata). A power model was used to analyze data in order to develop an allometric model. Furthermore, data validation was used to leave one out cross-validation (LOOCV), and assessing the difference between predicted and observed values used t-test. The results showed that bamboo biomass was allocated in culms, branches, and leaves at 48.14, 27.66, and 24.20%, respectively. Moreover, the percentage carbon content of culms, branches, and leaves was 55.64%, 50.67%, and 48.48%, respectively. The best allometric model to estimate total biomass was lnWD = -1.846 + 2.218 lnD and to estimate carbon stock was lnC = -2.504 + 2.225 lnD. In conclusion, the diameter at 60 cm from the base (D60) was the best predictor, and adding the predictor length of culm did not improve the allometric model significantly. Moreover, the predictor D0 – Dbh (1.3 m) did not differ significantly in estimating above-ground biomass and carbon stock. Furthermore, for practical purpose, the Dbh is recommended for use in measuring bamboo diameter in the field.